2020
DOI: 10.1155/2020/8928071
|View full text |Cite
|
Sign up to set email alerts
|

The Biomechanical Analysis of Magnitude and Direction of Force by Different Techniques of Thoracic Spinal Manipulation

Abstract: Background. Spinal manipulation (SM) has been widely recognized and used with success in health care fields for spinal joint dysfunction and pain. SM is a procedure that involves small amplitude manipulative thrusts performed with speed. These forces are complex three-dimensional (3-D) forces delivered to create forces and moments at the joint of interest to cause joint movements. The aim of this study was to conduct a 3-dimensional analysis of the magnitude and direction of the forces transmitted in 2 techniq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 27 publications
1
3
0
Order By: Relevance
“…In the current study, the vertical (F z ) preload and total peak forces (234.9 N (±36.5) and 462.1 N (±52.3), respectively) as well as the resultant preload and peak forces (260 N (±41.7) and 470.1 N (±46.4), respectively) measured at the clinicianparticipant interface were comparable to the ones previously reported in the literature. On the participant-table interface, previous studies using similar measurement instrument (i.e., force plate) reported preload forces between 157.7 N to 299.6 N and total peak forces of between 432.3 N and 625.4 N in adults younger than 30 years old (Cambridge Joo et al, 2020). Although trending towards the lower force range, comparable SMT preload and total peak forces were observed at the participant-table interface in this study.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…In the current study, the vertical (F z ) preload and total peak forces (234.9 N (±36.5) and 462.1 N (±52.3), respectively) as well as the resultant preload and peak forces (260 N (±41.7) and 470.1 N (±46.4), respectively) measured at the clinicianparticipant interface were comparable to the ones previously reported in the literature. On the participant-table interface, previous studies using similar measurement instrument (i.e., force plate) reported preload forces between 157.7 N to 299.6 N and total peak forces of between 432.3 N and 625.4 N in adults younger than 30 years old (Cambridge Joo et al, 2020). Although trending towards the lower force range, comparable SMT preload and total peak forces were observed at the participant-table interface in this study.…”
Section: Discussionsupporting
confidence: 77%
“…Fig. 2 presents preload and total peak force magnitudes of spinal mobilization and spinal manipulative therapy measured in the current study and reported in previous studies with younger adults (Cambridge et al, 2012;Forand et al, 2004;Herzog et al, 2001;Joo et al, 2020;Kirstukas and Backman, 1999;Snodgrass et al, 2006;Van Zoest and Gosselin, 2003) at the clinician-participant and participant-table interfaces for qualitative comparison.…”
Section: Qualitative Comparison With Previous Studiesmentioning
confidence: 99%
“…The initial peak force was set at 200 N, and increased in 100 N increment to reach a maximum peak force of 600 N. Each peak force was delivered using an increasing rate of force application ranging from 500 N/s to 2500 N/s, in 500 N/s increments. The force–time characteristics used in this study were based on the ones reported in the literature [ 17 19 ]. The lowest peak force was first delivered with the five different rates of force application, then the second-lowest peak force was delivered, and so on until the highest peak force was delivered with the highest rate of force application.…”
Section: Methodsmentioning
confidence: 99%
“…The initial peak force was set at 200 N and increased with an increment of 100 N for a maximum peak force of 600 N. Each peak force was delivered using an increasing rate of force application ranging from 500 N/s to 2500 N/s with increment of 500 N/s. The force-time characteristics used in this study were based on pro les reported in the literature [14,15]. The lowest peak force was rst delivered with the ve different rates of force application, then the second lowest peak force was delivered, and so on until the higher peak force was delivered with the highest rate of force application.…”
Section: Smt Applicationmentioning
confidence: 99%